Of Recent Australian Books - Merry, Bruce (LiNQ (Literature in North Queensland), 2016)
Day-Dreaming on Company Time by Robert Hood, The Cry by Carla Sari, Spilt Milk by Leah Kaminsky, This Goes With This by Peter Goldsworthy, Closed Doors by Karrinjeet Singh-Mahil, Black in Bright Sunlight by William Henderson and Snakes from Ireland by Linda Rooney are reviewed by Bruce Merry.